2021
DOI: 10.1037/apl0000675
|View full text |Cite
|
Sign up to set email alerts
|

Job search and employment success: A quantitative review and future research agenda.

Abstract: Job search is an important activity that people engage in during various phases across the life span (e.g., school-to-work transition, job loss, job change, career transition). Based on our definition of job search as a goal-directed, motivational, and self-regulatory process, we present a framework to organize the multitude of variables examined in the literature on job seeking and employment success. We conducted a quantitative synthesis of the literature to test relationships between job-search self-regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
182
2
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 120 publications
(193 citation statements)
references
References 206 publications
6
182
2
3
Order By: Relevance
“…A recent meta-analysis found that older workers face unique challenges in employing effective job search strategies as well as greater obstacles to reemployment ( Wanberg et al, 2016 ). Consistent with recommendations made by van Hooft et al (in press ), we suggest that successful job search and reemployment for older workers in the wake of COVID-19 should require greater attention to the individual’s job search skills and the socioeconomic, psychological, and technical capital available and used by the individual to identify job prospects. In addition to the considerations for future research suggested in previous sections (e.g., differential risk, mortality salience, and skill learning), practitioners should take these factors into consideration when designing reemployment interventions targeted at older workers.…”
Section: Pandemics Unemployment Job Search and Work Exitsupporting
confidence: 81%
“…A recent meta-analysis found that older workers face unique challenges in employing effective job search strategies as well as greater obstacles to reemployment ( Wanberg et al, 2016 ). Consistent with recommendations made by van Hooft et al (in press ), we suggest that successful job search and reemployment for older workers in the wake of COVID-19 should require greater attention to the individual’s job search skills and the socioeconomic, psychological, and technical capital available and used by the individual to identify job prospects. In addition to the considerations for future research suggested in previous sections (e.g., differential risk, mortality salience, and skill learning), practitioners should take these factors into consideration when designing reemployment interventions targeted at older workers.…”
Section: Pandemics Unemployment Job Search and Work Exitsupporting
confidence: 81%
“…Further, we tested the effectiveness of our self-compassion intervention in a mixed sample of job seekers, including new entrants, employed, and unemployed job seekers. Although job search is relevant in all these groups (e.g., Kanfer et al, 2001 ; Boswell et al, 2012 ; Van Hooft et al, in press ), future research is needed to examine to what extent our findings generalize to especially vulnerable populations such as long-term unemployed individuals. Possibly, stronger interventions are needed in such groups to obtain lasting effects.…”
Section: Discussionmentioning
confidence: 89%
“…Job search occurs in several stages of people’s lives, as reflected by job seeking research that has typically sampled students seeking for employment upon graduation, unemployed individuals looking for reemployment, and employed individuals seeking for a job change (e.g., Boswell et al, 2012 ; Van Hooft et al, in press ). Rather than restricting to a particular group, in the present study we included job seekers from all these groups.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations